Genomic diversity of bacteriophages infecting Microbacterium spp. - Jacobs-Sera, Deborah; Abad, Lawrence A; Alvey, Richard M; Anders, Kirk R; Aull, Haley G; Bhalla, Suparna S; Blumer, Lawrence S; Bollivar, David W; Bonilla, J Alfred; Butela, Kristen A; Coomans, Roy J; Cresawn, Steven G; et al. (PloS one, 2020)
The bacteriophage population is vast, dynamic, old, and genetically diverse. The genomics of phages that infect bacterial hosts in the phylum Actinobacteria show them to not only be diverse but also pervasively mosaic, and replete with genes of unknown function. To further explore this broad group of bacteriophages, we describe here the isolation and genomic characterization of 116 phages that infect Microbacterium spp. Most of the phages are lytic, and can be grouped into twelve clusters according to their overall relatedness; seven of the phages are singletons with no close relatives. Genome sizes vary from 17.3 kbp to 97.7 kbp, and their G+C% content ranges from 51.4% to 71.4%, compared to ~67% for their Microbacterium hosts. The phages were isolated on five different Microbacterium species, but typically do not efficiently infect strains beyond the one on which they were isolated. These Microbacterium phages contain many novel features, including very large viral genes (13.5 kbp) and unusual fusions of structural proteins, including a fusion of VIP2 toxin and a MuF-like protein into a single gene. These phages and their genetic components such as integration systems, recombineering tools, and phage-mediated delivery systems, will be useful resources for advancing Microbacterium genetics.
39 citations (Crossref) [2023-10-31] Place: United States Jacobs-Sera, Deborah. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Abad, Lawrence A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Alvey, Richard M. Department of Biology, Illinois Wesleyan University, Bloomington, Illinois, United States of America. Anders, Kirk R. Department of Biology, Gonzaga University, Spokane, Washington, United States of America. Aull, Haley G. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Bhalla, Suparna S. Department of Natural Sciences, Mount Saint Mary College, Newburgh, New York, United States of America. Blumer, Lawrence S. Department of Biology, Morehouse College, Atlanta, Georgia, United States of America. Bollivar, David W. Department of Biology, Illinois Wesleyan University, Bloomington, Illinois, United States of America. Bonilla, J Alfred. Department of Biology, University of Wisconsin-River Falls, River Falls, Wisconsin, United States of America. Butela, Kristen A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Coomans, Roy J. Department of Biology, North Carolina A&T State University, Greensboro, North Carolina, United States of America. Cresawn, Steven G. Department of Biology, James Madison University, Harrisonburg, Virginia, United States of America. D'Elia, Tom. Department of Biological Sciences, Indian River State College, Fort Pierce, Florida, United States of America. Diaz, Arturo. Department of Biology, La Sierra University, Riverside, California, United States of America. Divens, Ashley M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Edgington, Nicholas P. Department of Biology, Southern Connecticut State University, New Haven, Connecticut, United States of America. Frederick, Gregory D. Department of Biology and Kinesiology, LeTourneau University, Longview, Texas, United States of America. Gainey, Maria D. Department of Chemistry & Physics, Western Carolina University, Cullowhee, North Carolina, United States of America. Garlena, Rebecca A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Grant, Kenneth W. Department of Pathology, Wake Forest Baptist Health, Winston-Salem, North Carolina, United States of America. Gurney, Susan M R. Department of Biology, Drexel University, Philadelphia, Pennsylvania, United States of America. Hendrickson, Heather L. School of Natural and Computational Sciences, Massey University, Auckland, New Zealand. Hughes, Lee E. Department of Biological Sciences, University of North Texas, Denton, Texas, United States of America. Kenna, Margaret A. Department of Biological Sciences, Lehigh University, Bethlehem, Pennsylvania, United States of America. Klyczek, Karen K. Department of Biology, University of Wisconsin-River Falls, River Falls, Wisconsin, United States of America. Kotturi, Hari. Department of Biology, University of Central Oklahoma, Edmond, Oklahoma, United States of America. Mavrich, Travis N. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. McKinney, Angela L. Department of Biology, Nebraska Wesleyan University, Lincoln, Nebraska, United States of America. Merkhofer, Evan C. Department of Natural Sciences, Mount Saint Mary College, Newburgh, New York, United States of America. Moberg Parker, Jordan. Department of Microbiology, Immunology, & Molecular Genetics, University of California, Los Angeles, California, United States of America. Molloy, Sally D. Department of Molecular and Biomedical Sciences, University of Maine, Orono, Maine, United States of America. Monti, Denise L. Department of Biology, University of Alabama at Birmingham, Birmingham, Alabama, United States of America. Pape-Zambito, Dana A. Department of Biological Sciences, University of the Sciences in Philadelphia, Philadelphia, Pennsylvania, United States of America. Pollenz, Richard S. Department Cell Biology, Microbiology and Molecular Biology, University of South Florida, Tampa, Florida, United States of America. Pope, Welkin H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Reyna, Nathan S. Department of Biology, Ouachita Baptist University, Arkadelphia, Arkansas, United States of America. Rinehart, Claire A. Department of Biology, Western Kentucky University, Bowling Green, Kentucky, United States of America. Russell, Daniel A. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Shaffer, Christopher D. Department of Biology, University of Washington in St. Louis, St. Louis, Missouri, United States of America. Sivanathan, Viknesh. Howard Hughes Medical Institute, Chevy Chase, Maryland, United States of America. Stoner, Ty H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Stukey, Joseph. Biology Department, Hope College, Holland, Michigan, United States of America. Sunnen, C Nicole. Department of Biological Sciences, University of the Sciences, Philadelphia, Pennsylvania, United States of America. Tolsma, Sara S. Biology Department, Northwestern College, Orange City, Iowa, United States of America. Tsourkas, Philippos K. School of Life Sciences, University of Nevada, Las Vegas, Las Vegas, Nevada, United States of America. Wallen, Jamie R. Department of Chemistry & Physics, Western Carolina University, Cullowhee, North Carolina, United States of America. Ware, Vassie C. Department of Biological Sciences, Lehigh University, Bethlehem, Pennsylvania, United States of America. Warner, Marcie H. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Washington, Jacqueline M. Department of Natural Sciences, Nyack College, Nyack, New York, United States of America. Westover, Kristi M. Department of Biology, Winthrop University, Rock Hill, South Carolina, United States of America. Whitefleet-Smith, JoAnn L. Department of Biology & Biotechnology, Worcester Polytechnic Institute, Worcester, Massachusetts, United States of America. Wiersma-Koch, Helen I. Department of Biological Sciences, Indian River State College, Fort Pierce, Florida, United States of America. Williams, Daniel C. Department of Biology, Coastal Carolina University, Conway, South Carolina, United States of America. Zack, Kira M. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America. Hatfull, Graham F. Department of Biological Sciences, University of Pittsburgh, Pittsburgh, Pennsylvania, United States of America.
Keywords: *Actinobacteria/vi [Virology]; *Bacteriophages/ge [Genetics]; *Genetic Variation; *Genome; Viral; Actinobacteria; Article; Bacteriophages; Bacteriophages/cl [Classification]; Bacteriophages/ip [Isolation & Purification]; Base Composition; DNA base composition; DNA; Viral; DNA; Viral/ge [Genetics]; Genes; Viral; Genetic Variation; Genome; Viral; Genomics; Microbacterium; MuF like protein; Phylogeny; VIP2 toxin; Viral Fusion Proteins; Viral Fusion Proteins/ge [Genetics]; bacterial genome; bacterial strain; bacterial toxin; bacteriophage; capsid protein; classification; comparative genomics; controlled study; dept.bio; fusion protein; gene sequence; genetic variability; genetic variation; genetics; genome size; genomics; isolation and purification; nonhuman; nucleotide sequence; peer-reviewed; phylogeny; unclassified drug; virology; virus DNA; virus fusion protein; virus gene; virus genome; virus infection; virus isolation